Pharmacokinetics and safety of VALTOCO (NRL‐1; diazepam nasal spray) in patients with epilepsy during seizure (ictal/peri‐ictal) and nonseizure (interictal) conditions: A phase 1, open‐label study. (27th April 2020) - Hogan, Robert Edward; Tarquinio, Daniel; Sperling, Michael R.; Klein, Pavel; Miller, Ian; Segal, Eric B.; Rabinowicz, Adrian L.; Carrazana, Enrique
Abstract: Objective: To assess pharmacokinetics and safety of diazepam nasal spray (NRL‐1; VALTOCO®) in pediatric and adult patients with epilepsy in seizure and nonseizure states. Methods: A single dose of diazepam nasal spray (5, 10, 15, or 20 mg based on weight) was administered during each of two conditions (ictal/peri‐ictal and interictal condition) to patients 6‐65 years old with partial or generalized epilepsy with motor seizures or seizures with clear alteration of awareness; a second dose was permitted if needed for persistent seizures. Dosing could be interictal or ictal/peri‐ictal first, with a washout of ≥14 days. Blood samples for pharmacokinetic analysis were taken at prespecified time points. Treatment‐emergent adverse events (TEAEs), sedation, nasal irritation, nasal mucosal pain, and olfactory changes were assessed. Results: Of 57 patients in the study (mean age = 28.1 years [range = 6‐59], 54.4% female, 80.7% white), 49 were included in the primary pharmacokinetic analyses. Diazepam pharmacokinetic profiles were similar under both conditions, with approximately 2‐hour median time to mean (SD) maximum plasma concentrations of 164 (88) and 189 (110) ng/mL for ictal/peri‐ictal and interictal conditions, respectively; drug exposure during the first 6 hours postdosing was 532 (313) and 615 (368) hng/mL, respectively. Seventeen patients (29.8%) reported TEAEs, of whom eight (14%) had treatment‐related TEAEs, with those reported in ≥2 patients being dysgeusia (n = 3, 5.3%) and nasal discomfort (n = 2, 3.5%). One patient had serious TEAEs (recurrent seizures, metabolic encephalopathy), which were deemed unrelated to study treatment. No changes in respiratory rate were observed, nor were there clinically relevant changes in sedation, olfaction, nasal irritation, or acute nasal mucosal pain. Significance: The epileptic conditions (ictal/peri‐ictal, interictal) had minimal impact on diazepam nasal spray pharmacokinetics in patients with epilepsy. Therefore, diazepam nasal spray can be administered ictally and interictally. Diazepam nasal spray safety was consistent with the profile of diazepam.